DYNAMIC ANALYSIS OF THE MATHEMATICAL MODEL OF THE SPREAD OF CHOLERA WITH VACCINATION STRATEGIES - Abdul, Nur Safitri; Yahya, Lailany; Resmawan, R.; Nuha, Agusyarif Rezka (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
This research discusses the math model of spreading cholera disease with a mathematical strategy of math model constructed by considering a vaccination strategy. In addition, there is a population of hyperinfectious and lessinfectious bacteria so that the model of SVIR-BhiBli type, by. The model formed in the form of determination of fixed point, determination of basic reproductions numbers, analyzing the equilibrium point and sensitivity analysis. The equilibrium analysis produces two equilibrium points of a immediate-free equilibrium point of aceletotic local if and endemic equilibrium points will be stable local asymptotics if . Furthermore, numerical simulation that the increase in vaccination rate influences on the decline in value while increased rate of vaccine depreciation can increase the value of . In addition, sensitivity analysis shows that if the parameter is enhanced while other contrast parameters will contribute to the increase in value, as a result can increase the rate of transmission of cholera disease. Whereas if the parameter is enhanced while other contrast parameters will contribute to the decrease in value, as a result of the dissemination of the disease can be pressed very significantly.